1992
DOI: 10.1182/blood.v79.3.554.bloodjournal793554
|View full text |Cite
|
Sign up to set email alerts
|

The t(15;17) breakpoint in acute promyelocytic leukemia cluster within two different sites of the myl gene: targets for the detection of minimal residual disease by the polymerase chain reaction

Abstract: The retinoic acid receptor alpha (RAR alpha) and the myl gene are involved in the translocation breakpoint t(15;17)(q22;q21) in acute promyelocytic leukemia (APL). The majority of the breakpoint sites have been mapped within the second intron of the RAR alpha gene; however, the breakpoint sites on the myl gene are variable. Using primer sets derived from exon 2 or exon 3 of the RAR alpha gene and a primer derived from the myl cDNA, we were able to amplify the breakpoint sites of the fusion transcripts of all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Thus, the RA and DNA binding sites of RAR-ex are maintained in the fusion protein (25,34). These rearrangements were confirmed by other scientists (1,9,10,51) showing that they were found in almost all patients with APL and therefore involved in leukemogenesis. The response to RA seems to be associated with the expression of this aberrant PMLlRAR-ex mRNA, although the physiological reason for this association is unclear (51).…”
Section: Characteristics Of Acute Promyelocytic Leukemiasupporting
confidence: 76%
“…Thus, the RA and DNA binding sites of RAR-ex are maintained in the fusion protein (25,34). These rearrangements were confirmed by other scientists (1,9,10,51) showing that they were found in almost all patients with APL and therefore involved in leukemogenesis. The response to RA seems to be associated with the expression of this aberrant PMLlRAR-ex mRNA, although the physiological reason for this association is unclear (51).…”
Section: Characteristics Of Acute Promyelocytic Leukemiasupporting
confidence: 76%
“…23,24 In the early 1990s, several retrospective studies showed that reverse transcriptase-PCR (RT-PCR) analysis of the PML/RARα fusion gene product can detect residual leukemic cells during hematologic remission in patients with APL. [25][26][27][28] Furthermore, it was shown retrospectively that patients who remain PCR-positive after consolidation therapy 29 or who transformed from PCR-negative to PCRpositive 30 almost always experience a relapse. The GIMEMA group was the first to report prospectively about the natural history of molecular relapse.…”
Section: Postconsolidation Monitoringmentioning
confidence: 99%
“…The prognostic value of detecting MRD during clinical remission was initially suggested in Italy in 1992 131 and successively confirmed in numerous studies conducted in China, USA, Japan and several European countries. [132][133][134][135][136][137][138][139][140][141][142][143] Studies performed by using PCR assays capable of detecting one leukemic cell in a background of 10 3 -10 4 normal cells, agreed that a positive PCR test at completion of consolidation is strongly associated with impending clinical relapse. On the contrary, negative tests are not always associated with prolonged DFS and cure.…”
Section: Minimal Residual Disease (Mrd) and Molecular Relapsementioning
confidence: 99%
“…In fact, a sizable proportion of patients who had tested negative post-consolidation were reported in the same studies to have relapsed thereafter. [131][132][133][134][135][136][137][138][139][140][141][142][143] Notwithstanding, it is worth noting that no patients in long-term survival are found PCRpositive using this sensitivity threshold. [131][132][133][134][135][136][137][138][139][140][141][142][143] This clearly indicates that a status of PML/RAR␣ PCR negativity is our best presently available therapeutic goal.…”
Section: Minimal Residual Disease (Mrd) and Molecular Relapsementioning
confidence: 99%